Human Capital Formation, Life Expectancy and the Process of Economic Development - Matteo Cervellati; Uwe Sunde (Institute for the Study of Labor (IZA), 2002)
This paper presents a non-Malthusian theory of long-term development We model the interplay between the process of human capital formation, technological progress, and the biological constraint of finite lifetime expectancy. All these processes are interdependent and determined endogenously. The model is analytically solved and simulated for illustrative purposes. The resulting dynamics reproduce a long period of stagnant growth as well as an endogenous and rapid transition to a situation characterized by permanent growth. This transition can be interpreted as industrial revolution. Historical and empirical evidence is discussed and shown to be in line with the predictions of the model.
Keywords: J10; E10; O41; O40; O10; 330; long-term development; endogenous life expectancy; heterogeneous human capital; technological progress; industrial revolution; Entwicklungstheorie; Wachstumstheorie; Bildungsinvestition; Generationenbeziehungen; Sterblichkeit; Bevölkerungsökonomie; Dynamisches Gleichgewicht; Theorie